Foreign Institutional Investment Flows (FIIs) in Indian companies - Tripathi, Neeta (Indian Journal of Finance, 2008)
India has witnessed over a decade of FIIs portfolio flows and with each passing year, these flows have gained in their significance and have played a key role in the overall Indian economy. Investments by foreign institutional investors are typically synonymous with portfolio investments in India, with more than three months left in the current calendar year FIIs have invested a net of 10.47 billion in Indian equities, just 0.23 billion short of record high (10.7 billion) they clocked in the whole calendar year 2005. And this is at a time when the Bse sensex and the 50 share nifty of the national stock exchange are at their all time high. As the major portion of the FIIs investment goes in to equity markets it would have an impact on the shareholding pattern of Indian companies listed on the stock exchanges. About 95% of the FII funds are invested in stocks that comprise the key indices and half of it in the top five stocks that comprise the key indices, their influence on the performance of the stock market is immense. By taking quarterly shareholding pattern data of Bse sensex companies from Dec. 2001 to Dec.2006, we attempt to examine the changes if any, in the proportion of various shareholders in the overall shareholding pattern of these companies. We find that over the study period FIIs investment in Bse sensex companies is on the booming spree but it is still inadequate as compared to the size of our capital market and the prevailing favorable international economic conditions.